2012
DOI: 10.3109/09638288.2012.688922
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of the impact of a 12-week group exercise class for those moderately affected with multiple sclerosis

Abstract: Taking part in an exercise class was a positive experience for people with MS. Healthcare professionals should work with exercise professionals to provide feasible exercise opportunities to help those with MS benefit from therapeutic exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
102
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(109 citation statements)
references
References 19 publications
7
102
0
Order By: Relevance
“…The physical, psychological, and social benefits of exercise and physical activity reported in this study are consistent with other studies in pwMS [14,27,29,[32][33][34]. However, most of these studies demonstrated these positive impacts based on the experience of exercise and physical activity following an intervention program [27,29,32,33].…”
Section: Insights Into the Reasons Why Pwms Engage In Exercise And Phsupporting
confidence: 81%
See 1 more Smart Citation
“…The physical, psychological, and social benefits of exercise and physical activity reported in this study are consistent with other studies in pwMS [14,27,29,[32][33][34]. However, most of these studies demonstrated these positive impacts based on the experience of exercise and physical activity following an intervention program [27,29,32,33].…”
Section: Insights Into the Reasons Why Pwms Engage In Exercise And Phsupporting
confidence: 81%
“…However, most of these studies demonstrated these positive impacts based on the experience of exercise and physical activity following an intervention program [27,29,32,33]. This study highlighted that the perceived benefits associated with exercise and physical activity extended beyond the confines of an intervention program to also include activities carried out as part of a typical day.…”
Section: Insights Into the Reasons Why Pwms Engage In Exercise And Phmentioning
confidence: 97%
“…In contrast, Mostert and Kesselring 8 reported an immediate negative effect following cycling in people with MS, with increased muscle spasms. Qualitative evidence in studies of MS suggests that fatigue [9][10][11] and muscle pain 9 may result the day after exercise.…”
Section: Participantsmentioning
confidence: 99%
“…13 However, past evidence is unclear as to whether exercise may increase symptoms (ie, pain or fatigue) immediately following exercise in those with MS and CFS. 2,[9][10][11] Indeed, concern about a detrimental effect of exercise may deter people with these diseases from undertaking exercise, despite the absence of strong quantitative evidence that exercise may negatively affect symptoms over a longer period of time. In this study investigating the immediate effect of exercise on people with MS and CFS, we hypothesized that undertaking a 15-minute bout of aerobic exercise would increase pain and fatigue and decrease function for up to 24 hours following exercise.…”
Section: Participantsmentioning
confidence: 99%
“…Regular physical activity (PA) is beneficial for people with multiple sclerosis (MS) and has the potential to reduce the physical impact of MS after three months , Learmonth et al 2013. In the longer term, people with MS doing regular PA report less fatigue, fewer symptoms of depression and a greater quality of life (Stroud and Minahan 2009).…”
Section: Introductionmentioning
confidence: 99%